Hydraulic Modeling-Based Design of Retaining Wall Height for Flood Mitigation - Juliastuti, Yuliastuti; Wijayanti, Yureana; Fajar , Mohamad; Anda, Martin (Journal of Engineering and Sustainable Development, 2024)
The Bekasi River in Jakarta, Indonesia, faces significant flood risks due to high rainfall intensity, extensive urban development, and climate change. This paper aims to reduce the impact of floods by implementing efficient flood management measures, such as constructing retaining walls along the river.  The appropriate height and stability of retaining walls were determined by conducting hydrological and hydraulic analyses using HEC-HMS and HEC-RAS, respectively, accounting for maximum rainfall and flood discharge levels.  The results showed that the rainfall intensity in the Bekasi watershed with a return period of 2 years obtained a designed rainfall of 132 mm/hour using the Log Pearson III distribution, the maximum flood discharge for the return period Q50 is 1155 m3/second, the retaining wall design dimensions will be obtained 3-meter height with cross-section slope 0.002. Results indicated that almost all river channels overflow except near the Bekasi Dam, necessitating riverbank restoration and increased channel capacity. The paper highlights the need for reinforced retaining walls to protect the riverbank and improve flood resilience